Rekayasa Model Kebijakan Manajemen Otoritas Lokal dalam Eksploitasi Air Bersih Menggunakan Powersim Contructor - lmam Hanafi; Anwar Fitrianto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Stale authority intervention through public policies played an important role to fairly distributed and optimally utilized water resource. However. the local government as state representations could be fallen down on the execution. This research constructed by local authority policies model in exploiting clean water in Batu, East Java. This research model follows the quantitative paradigm. The created methodology model's foundations were based on systemic thinking methods and cognitive policies mapping by using Powerism Control Software. Constructed policies model was clean water exploitation. The model shows the common difficulties typology model. This model able to guide limitation, exploitation, and consumption of water resource management policies in order to create fairness, better service, competition, and give priority to public interest and hamper private dominations. Local government controls regarding to managing allocation (quantity, quality, duration), pricing, and water retributions were the prerequisite to ensure sufficient original district revenue while private companies acquire profit. Control and regulation by the government in term of clean water privatization were as a purpose to ascertain the long term benefits and eliminate any disadvantages.